High-precision HD spectroscopy near 1.53 μm - Gotti, Riccardo; Wójtewicz, Szymon; Marangoni, Marco; Gatti, Davide; Lamperti, Marco (Frontiers in Physics, 2024)
In this study, we report highly precise and accurate measurements of the P(5), P(6), and O(3) transitions of the 2–0 band of HD occurring at approximately 1.5 μm. HD spectra were acquired in the pressure range of 100–900 Torr using a cavity ring-down spectrometer linked to an optical frequency comb. The line-shape analysis was performed using the Hartmann–Tran profile in the so-called β-corrected version. For the P(5) transition, we improved the accuracy of previous line center frequency determinations by more than two orders of magnitude. Moreover, for the P(5) and P(6) line centers, the total standard uncertainty is below 3 MHz, similar to those provided by quantum electrodynamics predictions, making them useful for direct comparisons that might foster future improvements of the theoretical model.